Tinjauan Yuridis Pendirian Perseroan Terbatas Perorangan Oleh Usaha Mikro Kecil Berdasarkan Undang-Undang No 11 Tahun 2020 Tentang Cipta Kerja - Buana, Chriselda Febriany Kartika; Prananingtyas, Paramita (Fakultas Syariah INSURI Ponorogo, 2023)
Small Enterprises are growing rapidly in Indonesia, and play an important role in economic development in Indonesia. The emergence of Law Number 11 of 2020 concerning Job Creation has contributed to the ease of establishing a limited liability company for Small Enterprises. It supports the development of Small Enterprises, with the Job Creation Law the establishment of a company no longer requires a notary deed but can be registered easily on the official website of the Directorate General of Administration Of General Laws. The author wants to see how the establishment of a limited liability company by Small Enterprises is based on the Job Creation Law and see the differences in the procedure for independent establishment and establishment using a notarial deed. The benefit of this research is that to contributes to legal thinking and becomes a reference that related to the topic. The research method used is normative juridical, with a conceptual and statutory approach, secondary data collection, qualitative data types, with library study data collection techniques to be analyzed using descriptive analysis techniques. The results of the author's research on establishment by Small Enterprises are carried out on the website of the Directorate General of Administration Of General Laws and can be established by one person aged at least 17 years and fulfills the requirements in the form, which later if received will get a legal entity establishment certificate. The difference between those established with a notary is that the process of establishment with a notary deed is longer and has a deed of establishment, ownership by Small Enterprises as sole ownership, the legal basis on which Small Enterprises is based refers to the Job Creation Law while with a notary deed it is more Limited Liability Company Law.